Crossability and genetic analyses of Andrographis paniculata nees. populations using phenotypic and molecular markers - Valdiani, Alireza (2012)
Andrographis paniculata (AP) also known as the King of Bitters is a medicinal herb from the family Acanthaceae. The herb is blessed with curative effects such as anticancer, anti HIV, antiviral, anti diabetes and anti hepatitis, etc. To date AP has not been subjected to deep genetic scrutiny. The objective of this study was to evaluate the genetic mechanisms controlling the agromorphological and anticancer phytochemicals using classical and molecular methods in AP. The factors affecting low crossability as well as strategies to overcome this natural barrier were investigated in this exploration. For this purpose, a total of seven Malaysian AP accessions from six different states including Kelantan, Negeri Sembilan, Pahang (two accessions), Perak, Selangor and Terengganu were chosen to inspect the crossability and hybrid seed production using combined molecular and morpho-phenological approaches. The effect of cross combination, style length and time of hand-pollination on crossability was reflected in the significant chi-square value using nonparametric analysis based on Kruskal-Wallis test.For documentation of the genetic distance (GD) effect on crossability, the accessions were subjected to 55 Random Amplified Polymorphic DNA (RAPD) primers. However genetic distance based on Simple Matching method (SM) which ranged between 0.05 and 0.32 indicated the presence of a low genetic diversity among the studied accessions, but even a low GD decreased the rate of crossability. Phylogenetic analysis was performed using three chloroplast genes consisting of Internal Transcribed Spacer Region (ITS), Plastid matK regions, rps16 gene and trnL-F intron region along with phytochemical markers. The obtained results indicated that plastid genes are carrying a divergent nucleotide composition in the amplified fragments. Malaysian AP accessions are also significantly diverse (P≤0.01), in AG, NAG, and DDAG content. The novel part of this experiment came out with amplification of ITS and matK genes in this plant.As an important outcome, the effect of genetic distance revealed by the morphological characteristics on crossability of the accessions found to be neutral. Unlike the morphological markers, the phytochemical markers were negatively associated with crossability percentages. The GD revealed by the plastid genes based on Jukes-Cantor corrected distance, created the same results with phytochemical and RAPD markers. In another independent experiment, twenty-four microsatellite markers were applied on the AP accessions. These markers proved the presence of a fixed heterozygosity phenomenon in the herb. This achievement was remarkable as it happens when a population experiences repeated bottlenecks in population size. Another considerable upshot of the present study was introducing the Malaysian AP accessions as a cryptic species, while according to the changes in the microsatellite repeat motifs, they were genetically different than their Indian ancestors. The final research of this study evaluated the genetic base of the important traits using diallel analysis. The results demonstrated that both additive and non-additive gene effects contribute in controlling morphological and phytochemical traits of this species. The results also showed that most of morphological traits were under additive gene effects, in contrast, the phytochemical traits were affected by non-additive effects. Both negative and positive heteroses was estimated for different traits at the mid-parent and better-parent levels. Perhaps such results can draw a bright horizon for breeding of the prolific varieties in the future.